Myocardial work still reflect function while strain simply measure deformation when afterload increases. (14th October 2021) - Sletten, O J; Aalen, J M; Remme, E W; Khan, F H; Wajdan, A; Villegas, M; Hisdal, J; Smiseth, O A; Skulstad, H
Abstract: Introduction: Global longitudinal strain is recommended by the European Society of Cardiology to detect subclinical left ventricular (LV) dysfunction, but is markedly load-dependent. Myocardial work was recently introduced as a clinical tool to study LV function by pressure-strain analysis. Since myocardial work incorporates afterload, it is assumed to be less afterload-dependent than strain, but the relationship with afterload is incompletely understood. Hypothesis: Myocardial work is a better tool than strain, to measure myocardial function during elevated afterload. Methods: In eleven anesthetized dogs, LV volume and longitudinal strain were measured by sonomicrometry, and pressure by micromanometry. Myocardial work was calculated by pressure-strain analysis. Additionally, stroke work was calculated as the area of the pressure-volume loop. Afterload was instantly increased by aortic constriction using a pneumatic cuff around the ascending aorta. Measurements were performed at baseline, during moderate- and marked afterload elevations. Results: Table 1 summarizes the results. LV pressure (LVP) successively increased with moderate and marked afterload elevation, while longitudinal strain was successively reduced. Myocardial work and stroke work, on the other hand, increased with moderate afterload elevation, but was then reduced at marked afterload increase (Figure 1 and Table 1). Stroke volume and ejection fraction corresponded to strain and were reduced with afterload elevation. Conclusions: Longitudinal strain and myocardial work have qualitatively different responses to increased afterload. While moderate changes in afterload cause reductions in strain that can be falsely interpreted as reductions in contractility, myocardial work increases as it incorporates the increased workload at moderately elevated afterload. Funding Acknowledgement: Type of funding sources: Public Institution(s). Main funding source(s): The Norwegian Health Association